Myelin composition of spinal cord in a model of amyotrophic lateral sclerosis (ALS) in SOD1G93A transgenic rats - Niebroj-Dobosz, Irena; Rafałowska, Janina; Fidziańska, Anna; Gadamski, Roman; Grieb, Paweł (Folia Neuropathologica, 2007)
We present the results of biochemical and electron microscopic (EM) examinations of the spinal cord myelin from SOD1G93A transgenic Sprague Dawley rats in the early and late symptom-free period of the disease (60 and 93 days of life) and after four-leg paralysis has occurred (120 days of life). Biochemical and ultrastructural changes of myelin started already in the symptom-free period and become most pronounced in the paralyzed animals. Biochemical examinations indicated a decrease of lipids, phospholipids, cholesterol and cerebrosides. The pattern of particular phospholipids was in the normal range. A progressive decrease of the percentages of proteolipid, DM-20 and Wolfgram proteins was evident. Myelin basic proteins I and II were less affected. In EM, massive myelin disorganization was observed.